DECISION SUPPORT SYSTEM FOR SELECTING ATHLETE CANDIDATES IN PSTI BANTUL USING PROFILE MATCHING METHOD BASED ON WEB - Eko Setyawan; Muhammad Fairuzabadi; Puji Handayani Putri (JTH: Journal of Technology and Health, 2023)
PSTI Bantul is a sepak takraw club which is active in developing DIY sepak takraw athletes from an early age, teenagers and adults. A Decision Support System is an information system to assist in making decisions related to semi-structured and unstructured problems. The method used is profile matching, which utilizes technology to facilitate user access and interaction. Users can see the general profile matching calculation results in each period so that the selection process becomes more open and transparent, providing fair opportunities for each prospective athlete. From the research results, this system runs according to the function that has been designed, which is able to provide information on selection results from each period.